2020
DOI: 10.1177/0969733020906593
|View full text |Cite
|
Sign up to set email alerts
|

Moral distress: Developing strategies from experience

Abstract: Background Moral distress was first described by Jameton in 1984, and has been defined as distress experienced by an individual when they are unable to carry out what they believe to be the right course of action because of real or perceived constraints on that action. This complex phenomenon has been studied extensively among healthcare providers, and intensive care professionals in particular report high levels of moral distress. This distress has been associated with provider burnout and associated conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 37 publications
1
63
0
5
Order By: Relevance
“…Fortunately, nurses consider formal ethics support as helpful in resolving moral distress. 34 We found that disagreements on end-of-life care as a root cause of moral distress were not quite as prominent in paediatric oncology units as those reported in critical care settings. 8,21 Although grief and loss are unavoidable in paediatric oncology nursing, 35 not all emotionally distressing situations generate moral distress.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Fortunately, nurses consider formal ethics support as helpful in resolving moral distress. 34 We found that disagreements on end-of-life care as a root cause of moral distress were not quite as prominent in paediatric oncology units as those reported in critical care settings. 8,21 Although grief and loss are unavoidable in paediatric oncology nursing, 35 not all emotionally distressing situations generate moral distress.…”
Section: Discussionmentioning
confidence: 67%
“…Maybe the repetitive exposure to distressing situations over time is not solely disadvantageous. According to Helmers et al, 34 it can broaden the understanding of different ways of dealing with ethical dilemmas, leading to a wider perspective on ethical issues that in turn can be helpful in diminishing experiences of moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…The gap between what students have learned and the actions they take in practice may lead to "moral distress" [12]. Graduated nurses also experience moral distress [13][14][15]. In a systematic review by Sasso et al [4], the authors highlighted that further research is needed to improve our understanding of the phenomenon of moral distress.…”
Section: Introductionmentioning
confidence: 99%
“…Helmers et al [ 13 ] found that moral distress was a common experience in nursing practice, with both social and environmental stressors, such as lack of empathy or differences in opinion about care, prioritizing, or resource allocation. It seems that we cannot eliminate moral distress, thus we need to foster personal growth that enables nurses and students to better address and manage the situations of moral distress associated with practice [ 10 , 13 ]. Consequently, we need more knowledge about the types of difficult situations nurses encounter in their work.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the emotional distress associated with living and coping with an ethical conflict, strategies like daily debriefings and consultations with a psychologist about the complexity of relationships with older patients and their families could be implemented ( Choe et al., 2018 ; Dufrene & Young, 2014 ; Pileggi et al., 2014 ). According to Helmers et al. (2020) and Stolt et al.…”
Section: Discussionmentioning
confidence: 99%